eIF6 affects the occurrence and development of esophageal cancer - Cong-Gai Huang; Xin Zhou; Ran Huang; Hui-Ling Zhang; Chen-Xi Li; Fei Du; Hong Lei; Qiong Dai; Zhi-Hui Yang (Molecular Biology Reports, 2026)

Process-aware SSA-Conv-PatchTST for robust multi-horizon aeration-demand forecasting in full-scale wastewater treatment plants - Ran Song; Xiaole Mei; Xinhua Jiang; Xuelei Ma; Muqier Wudan; Wenlong Bai; Hao Lin; Zhi Li; Shengbin Gao (Journal of Water Process Engineering, 2026)

Multi-scale analysis of patterns, risks, and mechanisms of edaphic antibiotic resistance genes on the Qinghai-Tibet Plateau: Integrating regional and national perspectives - Weiguo Zhang; Guangcan Ran; Pengfu Li; Junxian Ke; Shenyang Ji; Yan Gao; Rongjun Bian; Zhi Wang (Environmental Pollution, 2026)

Attribute-probability-constrained facies-consistent ES-MDA geostatistical inversion for acoustic impedance - Zhi-Fang Ran; Guo-Fa Li; Hao Li; Wei-Wei Gu; Yin-Quan Hao (Applied Geophysics, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

PD-1/PD-L1 inhibitor induces systemic inflammation and alters cardiac lipid metabolism in C57BL/6 J mice - Cong Ye; Zhi-Ting Jiang; Chen Yan; Xin-Ran Li; Yu-Hua Zhu; Ling-Yu Zeng; Lan Luo (Human Cell, 2026)

The effect of high-pressure homogenization pressure on the 3D printing of potato protein secondary emulsion - Yi Liu; Hao-ran Chen; Ao-xue Qie; Chong-hao Bi; Zhi-gang Huang; Quan-lai Li; Qiu-yue Du (Food and Bioproducts Processing, 2026)

A simple method to estimate seismic subsidence in soft soil under amplitude non-stationary seismic action - Gan-Ling Xian; Jing-Yan Lan; Li-Chun Chen; Yong-Zhi Wang; Lei Wang; Zhao-Ran Wu (Engineering Geology, 2026)

Structure-Constrained Prior Ensembles for ES-MDA Post-Stack Acoustic Impedance Inversion - Zhi-fang Ran; Yin-quan Hao; Pin Zhang; Weiwei Gu; Guo-fa Li (Applied Geophysics, 2026)

Retail wet markets, food handlers, and hospitalised patients as nodes in a shared non-typhoidal Salmonella ecosystem: a one health molecular epidemiological pilot study in Wuhan, China - Feng Tang; Zhi Chen; Shiyong Deng; Xiaomei Wang; Xuyang Gong; Ran Li; Lei Xi; Changzhen Li; Baoxiang Wang; Wanjun Luo (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Seismic data processing key technology for coalbed methane reservoir - Ming Zhang; Bao-yin Zhao; Zhi-fang Ran; Wen-wu Shi; Hao Li; Kai-long Wu; Gen-yang Tang (Applied Geophysics, 2026)

Molecularly imprinted polymers-based magnetic CoFe oxides nanozyme for the removal of Staphylococcus aureus and label-free quantitative detection - Jing Liu; Ran Chen; Jing-Wen Chen; Shao-Bo Li; Yue-Jie Li; Yong-Fu Huang; Zhi-Bin Chen; Li Li (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

The gut as a reservoir of drug-resistant pathogens: Mechanisms of ENR-driven horizontal gene transfer in aquaculture - Bian-Hao Zeng; Ping Li; Hao-Ran Zhang; Bang-Hua Xia; Bin Liu; Ling-Ming Kong; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Late Mesozoic exhumation of metamorphic core complexes from the Xiaoqinling to Dabie orogen, central China: a record of Paleo-Pacific slab rollback - Wan-Shan Lei; Yu Duan; Zhi-Qiang Liu; Ran Wang; Hai-Dong Zhang; San-Zhong Li (International Geology Review, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Ni/Zr co-doping strategy to promote cyclic performance of CaO-based materials for thermochemical energy storage: Experimental and first-principles insights - Zhu-yu Li; Le-ran Li; Jing-yi Liu; Qi Niu; Zhi-mo Fang; Ji-hong Li; Kai Li; Qiang Lu (Chemical Engineering Journal, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Sparse spike inversion with parity decomposition and stratal dip constraints - Jian-lei Zhang; Zhi-fang Ran; Fu-min Li; Guo-fa Li (Applied Geophysics, 2025)

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

P-CSF: Polar coordinate cloth simulation filtering algorithm for multi-type tunnel point clouds - Zhiyang Zhi; Bingtao Chang; Yuan Li; Zhigang Du; Yipeng Zhao; Xiaodong Cui; Jiahuan Ran; Aiguang Li; Wuming Zhang (Tunnelling and Underground Space Technology, 2025)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

Suitable water management improving cold tolerance of rice seedlings - Qiang Zhang; Feng Wen; Bingbing Li; Zhi Li; Zhenjiang Wu; Xu Kuang; Guilong Yu; Xiangchen Liu; Yang Hu; Yuchen Zhang; Ran Yu; Lingling Ding; et al. (Cereal Research Communications, 2024)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Pagoda solar evaporators with an alternating hot-cold pattern for rapid, scaling-free desalination of hypersaline brines - Zhenwei Wu; Kai Li; Ran Deng; Yu-Ren Xue; Hao-Nan Li; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2024)

Green wood bio-adhesives from cellulose-derived bamboo powder hydrochars - Yong-Xing Chen; Han-Song Zhu; Fan Gao; Huan-Ran Xiong; Huan Yang; Zhi-Xiang Xu; Pei-Gao Duan; Li-Jun Zheng; Sameh M. Osman; Rafael Luque (Chemical Engineering Journal, 2024)

Taming the anchor and conversion of polyselenides with a self-reinforcing host in lithium–selenium batteries - Hongyan Li; Wenda Dong; Yueqiang Cao; Tarek Barakat; Marvin Laboureur; Mao-Jin Ran; Zhi-Yi Hu; Hongxian Zhang; Cheng-Bin Jin; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Soil legacy phosphorus and loss risk in subtropical grasslands - Ran Zhi; Elizabeth H. Boughton; Haoyu Li; Daniel F. Petticord; Amartya Saha; Jed P. Sparks; K. Ramesh Reddy; Jiangxiao Qiu (Journal of Environmental Management, 2024)

Effect of recycled polypropylene on migration of six processing aids in polypropylene film to milk - Yi-Qi Liu; Ze-Kun Li; Hao-Ran Zhang; Zhi-Wei Wang; Chang-Ying Hu (Food Packaging and Shelf Life, 2024)

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Differential dissolution of biogenic silica significantly affects the utility of sediment diatoms as paleoceanographic proxies - Lihua Ran; Martin G. Wiesner; Yuzhao Liang; Wen Liang; Lanlan Zhang; Zhi Yang; Hongliang Li; Jianfang Chen (Limnology and Oceanography, 2024)
Diatoms and biogenic silica (biogenic Si) in sediments are commonly analyzed as paleoceanographic environmental indicators. However, the correspondence between these sedimentary components and their counterparts in the water column above can vary over time and space. This study, undertaken in the northern South China Sea, compares diatoms and biogenic Si in sinking particles from the water column with those in surface sediments below. The results indicate substantial losses of diatoms and biogenic Si during sinking and burial, along with changes in diatom assemblages. About 6% of diatoms sinking from 1000 m depth are estimated to be preserved in sediments: 32% are recycled in the water column and 62% are lost at the sediment–water interface. Approximately, 12% of biogenic Si is preserved in sediments: 6% is remineralized in the water column and 82% is lost at the sediment–water interface. The differences between diatom and biogenic Si preservation and remineralization are likely due to differences in dissolution resistance among the various diatom species and between diatoms and other silicifiers (e.g., radiolarians), along with effects of lateral transport. This variability introduces uncertainties into paleoceanographic inferences made from these two proxies from the sediments. Thalassionema nitzschioides was found to dominate sediment assemblages, which we attribute to its great resistance to dissolution, and to be negatively correlated with diatom sinking fluxes. These properties suggest that in the northern South China Sea, T. nitzschioides may potentially be useful as an indicator of low paleoproductivity (e.g., as seen during strong El Niño events).

Phosphorus species transformation and recovery in deep eutectic solvent-assisted hydrothermal carbonization of sewage sludge - Rui Dou; Fan Gao; Yi Tan; Huan-Ran Xiong; Zhi-Xiang Xu; Sameh M. Osman; Li-Jun Zheng; Rafael Luque (Sustainable Chemistry and Pharmacy, 2024)

Hydrochar-based facile and greenwood bio-adhesives production from distilled spent grain - Zhi-Xiang Xu; Huan-Ran Xiong; Rui Dou; Yi Tan; Yong-Xing Chen; Li-Jian Leng (Chemical Engineering Journal, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

A long way to go: impacts of urbanization on migrants’ livelihoods and rural ecology in less industrialized regions - Zhi-qi Zhang; Ming-jing Li; Wen-jun Li; Yi-ran Wei; Yi-lu Shi (Journal of Mountain Science, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Neiella litorisoli sp. nov., an alginate lyase: producing bacterium from South China Sea, and proposal of Echinimonadaceae fam. nov. in the order Alteromonadales - Jing-Ran Sun; Kun-Lian Mo; Xue Li; Yong-Hua Hu; Zhi-Yuan Liu; Hui-Qin Huang (Archives of Microbiology, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Sustainable utilization of residual grass: effect of anaerobic storage days on chemical composition, fermentation performance, microbial community, and functional profiles of Pennisetum giganteum - Jie Zhao; Zhao-Di Jing; Xue-Jing Yin; Jun-Feng Li; Zhi-Hao Dong; Si-Ran Wang; Tao Shao (Environmental Science and Pollution Research, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Maximum displacement prediction of composite floor system under falling impact - Jing-Zhou Zhang; Guo-Qiang Li; Ying-Zhi Sun; Jing Sun; Zhi-Wei Yu; Ran Feng (Engineering Structures, 2023)

High-strength, self-initiated, wide pH range of underwater adhesive suitable for different severe environments - Junyu Ren; Guanben Du; Sichen Liu; Hongxing Yang; Xin Ran; Chang Liu; Tongda Liu; Zhi Li; Xiaojian Zhou; Wei Gao; Bei Zhou; Long Yang (Chemical Engineering Journal, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

Sediment Resuspension as a Major Contributor to Sinking Particles in the Northwestern South China Sea: Evidence From Observations and Modeling - Lihua Ran; Wentao Ma; Martin G. Wiesner; Yuntao Wang; Jianfang Chen; Lanlan Zhang; Zhi Yang; Jingjing Zhang; Hongliang Li; Jian Ren; Rong Xiang; Erick Fredj (Frontiers in Marine Science, 2022)
The lateral advection of sinking particles is a well-known phenomenon in the South China Sea (SCS) and has a significant impact on the estimation of the efficiency of the biological carbon pump. However, little is known about the sources and pathways of sinking particles. Here, we present benthic and freshwater diatom fluxes and relative abundances collected by a sediment trap deployed at a water depth of 1,000 m and more than 500 m above the seafloor in the northwestern SCS, indicating that laterally transported resuspended sediment accounts for a significant part of the particle flux to the deep sea. A Lagrangian particle tracking model (LPTM) revealed that the resuspended particles likely originated from the neighboring continental slope, approximately 12–145 km to the west of the study site. Sediment trap observations and the LPTM together indicated that the impact of resuspended sediment occurred mainly in the deep water, and especially strong sediment resuspension was related to summer monsoon-induced coastal upwelling. The results suggest that particle resuspension has an important impact on the biological pump as well as on paleoenvironmental reconstructions of the SCS.

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Performances of six eupelmid egg parasitoids from China on Japanese giant silkworm Caligula japonica with different host age regimes - Yong-Ming Chen; Xing-Ran Qu; Tian-Hao Li; Asim Iqbal; Xingeng Wang; Zhi-Yong Ren; Nicolas Desneux; Lian-Sheng Zang (Journal of Pest Science, 2021)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

A threshold stresses-based permeability variation model for microcracked porous rocks - Xing Li; Yi-Feng Chen; Kai Wei; Ran Hu; Zhi-Bing Yang (European Journal of Environmental and Civil Engineering, 2020)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Sources and transformations of nitrogen in the South China Sea: insights from nitrogen isotopes - Zhi Yang; Jianfang Chen; Min Chen; Lihua Ran; Hongliang Li; Peng Lin; Yong Zhu; Chunsheng Wang; Zhongqiang Ji; Jingjing Zhang (Journal of Oceanography, 2018)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

The complete chloroplast genome sequence of Leersia perrieri of the rice tribe Oryzeae, Poaceae - Ge-Ran Hutang; Li-Zhi Gao (Conservation Genetics Resources, 2017)

Prediction of brittleness based on anisotropic rock physics model for kerogen-rich shale - Ke-Ran Qian; Zhi-Liang He; Ye-Quan Chen; Xi-Wu Liu; Xiang-Yang Li (Applied Geophysics, 2017)

Thermal ecology of three coexistent desert lizards: Implications for habitat divergence and thermal vulnerability - Shu-Ran Li; Yang Wang; Liang Ma; Zhi-Gao Zeng; Jun-Huai Bi; Wei-Guo Du (Journal of Comparative Physiology B, 2017)

Overexpression of the nitrate transporter, OsNRT2.3b, improves rice phosphorus uptake and translocation - Huimin Feng; Bin Li; Yang Zhi; Jingguang Chen; Ran Li; Xiudong Xia; Guohua Xu; Xiaorong Fan (Plant Cell Reports, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Low precipitation aggravates the impact of extreme high temperatures on lizard reproduction - Yang Wang; Zhi-Gao Zeng; Shu-Ran Li; Jun-Huai Bi; Wei-Guo Du (Oecologia, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Paenibacillus herberti sp. nov., an endophyte isolated from Herbertus sendtneri - Guan Nan Guo; Xun Zhou; Ran Zhao; Xin Yao Chen; Zhi Ling Chen; Xue Dong Li; Yan Hong Li (Antonie van Leeuwenhoek, 2015)

A theoretical analysis of basin-scale groundwater temperature distribution - Ran An; Xiao-Wei Jiang; Jun-Zhi Wang; Li Wan; Xu-Sheng Wang; Hailong Li (Hydrogeology Journal, 2015)

Chryseobacterium polytrichastri sp. nov., isolated from a moss (Polytrichastrum formosum), and emended description of the genus Chryseobacterium - Xin Yao Chen; Ran Zhao; Zhi Ling Chen; Lei Liu; Xue Dong Li; Yan Hong Li (Antonie van Leeuwenhoek, 2015)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)